(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the disease and treatment results of mechanically ventilated patients in the pediatric intensive care unit at Nghe An Obstetrics and Pediatrics Hospital. Subjects and research methods: A descriptive cross-sectional study of 200 mechanically ventilated patients in the PICU in 2022. Results: Ventilated children with diseases of the respiratory system (chapter X) accounted for the highest (30%), followed by certain infectious and parasitic diseases (chapter I) accounting for 16%. Diseases of the nervous system (chapter VI), and diseases of the circulatory system (chapter IX) accounted for 10.5% and 9.5%, respectively. In ventilators due to respiratory diseases, pneumonia was the most common, accounting for 73.3%, and pleural effusion and acute respiratory distress syndrome accounted for 6.7%. There were 19 mechanically ventilated patients due to diseases of the cardiovascular system, in which primary hypertension accounted for the highest rate of 31.6%, followed by myocarditis and arrhythmias, both accounting for 21.1%. 21 patients with mechanical ventilation due to nervous system diseases, in which meningoencephalitis did not account for the highest rate of 57.1%, followed by myasthenia gravis took up 23.8%, and epilepsy took up 14.3%. The mortality rate accounted for 49,5%, the survival rate was 37.5%, and the transferred rate to a high level was 13%. Conclusion: The ventilator-associated pattern of the respiratory system and certain infectious and parasitic diseases was high. The mortality rate of ventilator patients is still high.